Cost-effective differentiation of hepatocyte-like cells from human pluripotent stem cells using small molecules. (November 2015) - Tasnim, Farah; Phan, Derek; Toh, Yi-Chin; Yu, Hanry
Abstract: Significant efforts have been invested into the differentiation of stem cells into functional hepatocyte-like cells that can be used for cell therapy, disease modeling and drug screening. Most of these efforts have been concentrated on the use of growth factors to recapitulate developmental signals under in vitro conditions. Using small molecules instead of growth factors would provide an attractive alternative since small molecules are cell-permeable and cheaper than growth factors. We have developed a protocol for the differentiation of human embryonic stem cells into hepatocyte-like cells using a predominantly small molecule–based approach (SM-Hep). This 3 step differentiation strategy involves the use of optimized concentrations of LY294002 and bromo-indirubin-3'-oxime (BIO) for the generation of definitive endoderm; sodium butyrate and dimethyl sulfoxide (DMSO) for the generation of hepatoblasts and SB431542 for differentiation into hepatocyte-like cells. Activin A is the only growth factor required in this protocol. Our results showed that SM-Hep were morphologically and functionally similar or better compared to the hepatocytes derived from the growth-factor induced differentiation (GF-Hep) in terms of expression of hepatic markers, urea and albumin production and cytochrome P450 (CYP1A2 and CYP3A4) activities. Cell viability assays following treatment with paradigm hepatotoxicants Acetaminophen, Chlorpromazine, Diclofenac, Digoxin, Quinidine and Troglitazone showed that their sensitivity to these drugs was similar to human primary hepatocytes (PHHs). Using SM-Hep would result in 67% and 81% cost reduction compared to GF-Hep and PHHs respectively. Therefore, SM-Hep can serve as a robust and cost effective replacement for PHHs for drug screening and development.